ANALYSIS OF THE LEVEL OF PROCRASTINATION OF FKIP UNISRI STUDENTS - Sholikhah, Linda Dwi; Suryanti, Hera Heru Sri (Jurnal Konseling Pendidikan Islam, 2024)
This research aims to determine the level of student academic procrastination. The research method used is quantitative research using surveys. The survey results showed that from a sample of 109 students, the results were: Low academic procrastination category, namely: 0 students, Medium academic procrastination 98 students (89.90%), High academic procrastination 11 students (10.09%). Based on the survey results, the results showed that the majority of students' level of academic procrastination was in the medium category and some were in the high academic procrastination category. Based on observations, namely: students do assignments at a tight time to submit assignments, and sometimes some students are late in submitting assignments.